Improved charging phenomenon with a modified barrier structure for flexible displays fabricated on polyimide substrates. Issue 19 (24th May 2021) - Kim, H.J.; Park, J.M.; Byun, C.W.; Bak, S.R.; Jung, Y.J.; Han, C.H.; Yoo, J.M.; Kim, S.K.; Choi, P.H.; Lee, J.H.; Song, J.K.; Choi, B.D.
Abstract: In a previous study, the authors investigated that abnormal V th behaviour could occur due to polyimide charging when a voltage was applied to the gate in thin film transistors fabricated on polyimide substrates. The authors propose a barrier structure that could prevent this charging effect when fabricating flexible thin film transistors on polyimide substrates. The barrier layer was changed to an SiOCH/SiO2 double layer to reduce the influence of fluorine ions generated in PI by negative bias temperature stress. To confirm the effect of the SiOCH layer, Al/PI/SiO2 /Al, Al/PI/SiOCH/SiO2 /Al metal‐insulator‐metal capacitors were fabricated and electrical properties were measured. When bias stress was applied, changes in current and capacitance were observed only in the device with a single SiO2 barrier layer. In addition, it was confirmed through secondary ion mass spectrometry measurements that the Si–CH3 bonds in the SiOCH layer were replaced with Si–F bonds by the fluorine ions originating from PI. It was also verified that the abnormal behaviour of V th did not occur after negative bias temperature stress of the thin film transistor fabricated using an SiOCH/SiO2 double layer.